Phytochemical Investigation of Mastigophora diclados: Isolation of a Herbertene-Type Sesquiterpenoid - Ardiansyah, Ferry Indar; Tlali, Moeketsi Freddie (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to isolate and characterize secondary metabolite compounds from the ethyl acetate extract of the liverwort Mastigophora diclados collected in Indonesia using chromatographic separation and spectroscopic analysis. Methodology: This study employed an experimental laboratory design using maceration extraction with n-hexane and ethyl acetate. Isolation was conducted using column chromatography and thin-layer chromatography (silica gel 60 GF254). Instruments included rotary evaporator (Eyela N-1000), water bath (Eyela SB-1000), and ¹H-NMR spectrometer (JEOL 500 MHz). Data were analyzed through spectral comparison and phytochemical screening methods. Main Findings: The ethyl acetate extract yielded 41.78 g (1.98%). Phytochemical screening indicated the presence of terpenoids. Two pure compounds were obtained (III-B: 8 mg; IV-B: 4 mg) with Rf 0.44. Compound III-B showed a melting point of 152–154 °C. ¹H-NMR analysis revealed characteristic signals of four methyl groups and olefinic protons, indicating a herbertene-type sesquiterpenoid structure. Novelty/Originality of this study: This study is the first to report the isolation and structural characterization of secondary metabolites from Indonesian Mastigophora diclados. It reveals a herbertene-like compound with slight spectral variations, suggesting a potential new derivative influenced by geographical factors, thereby contributing to bryophyte chemotaxonomy and expanding natural product research in tropical regions.